Urgensi Optimalisasi Pembiayaan Mudharabah sebagai Core Product Perbankan Syariah Indonesia - Emy Widyastuti (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2020)
This study aims to examine the urgency of optimizing mudharabah financing as a core product of Islamic banking in Indonesia. Mudharabah financing is one of the financing products in Islamic banking that uses a profit sharing scheme (PLS-Profit and Loss Sharing). This profit sharing becomes the identity of an Islamic bank and distinguishes it from the interest on conventional banks. In practice, mudharabah financing is rarely implemented and has the smallest proportion of the total financing channeled by Islamic banking. The method used in this research is exploratory descriptive qualitative to examine the urgency of optimizing the Islamic banking mudharabah financing in Indonesia. OJK (Financial Services Authority) data for 2019 shows the amount of mudharabah financing disbursed amounted to 5.41 trillion while murabahah financing amounted to 121.04 trillion of the total financing amounting to 219.67 trillion. This alarming condition requires all parties to participate in efforts to optimize mudharabah financing as productive financing which is believed to be ideal by fiqh experts because of the fairness in it. Keywords: mudharabah financing, Islamic banking, Islamic economics